Planning and Budgeting: The Study of Village Financing Process In Balige Subdistrict - Lumbantoruan, Dwi Lauran; Mulyani, Sri (Universitas Padjadjaran, 2019)
This study aims to understand the management of village funds, especially in the planning and budgeting processes. The focus of the study was on the suitability of the planning and budgeting processes carried out by village governments with applicable regulations, namely the Minister of Home Affairs Regulation (Permendagri) No. 114 and 113 the year 2014. The study employed qualitative methods, and the collection of data was conducted using interview techniques. The study was taken place in Lumban Gaol Village and Parsuratan Village in Balige Subdistrict, South Toba of Indonesia. The results of the study indicate that the planning and budgeting process is not fully following the regulations, especially in Parsuratan Village. Several stages in the planning and budgeting process were not carried out in the village of Parsuratan. This mismatch of the planning and budgeting process is because village officials do not yet have sufficient understanding of the matter. There are also differences in the intensity of community involvement in the planning and budgeting process in those two villages. This difference results in the different quality of the planning documents and the budget. The competency of village officials and intense community involvement play a significant role in the better planning and budgeting process made by the village government